Perancangan Pengalaman Pengguna Aplikasi Knowledge Management System UMKM menggunakan Metode Human Centered Design (Studi Kasus: UMKM Bogor) - Luthfi Pratama Nugraha; Riswan Septriayadi Sianturi; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Knowledge Management System of UMKM Bogor application is an application designed with the aim of disseminating uneven knowledge and knowledge management for Bogor UMKM actors. This application was made based on the needs of the Bogor One Stop Integrated Service and Investment Service (DPMPTSP) with the Bogor UMKM Forum. This study aims to design the User Experience for Bogor UMKM Knowledge Management System application so that the application created has good results for its users in terms of usability and user experience. The method used to carry out the design is Human-Centered Design (HCD) which consists of stages of user context analysis, user needs analysis, solution design, and solution design evaluation. The user requirements analysis process results in one user and one stakeholder. The user needs analysis process found that the Bogor UMKM KMS system had 15 functional requirements and 3 non-functional requirements. The solution design process is generated by wireframes, screen flows, mockups, and prototypes. The solution design evaluation process is carried out using usability testing. The test results show the level of effectiveness of the design that has been created reaches a value of 70.0%, the level of efficiency reaches a value of 0.06 goals/second, and the level of user satisfaction as measured by SUS reaches a value of 78.75 (grade B). The results of the UEQ questionnaire show the attractiveness aspect value 1.87, perspicuity 1.88, efficiency 1.93, dependability 1.78, stimulation 1.30, and novelty 1.08. User experience has good results because all aspects of UEQ are above average.